Students’ satisfaction of MARA College management services, learning environment and the effect on learning motivation - Amzat, Ismail Hussein; Abd Razak, Hairi Waznati Azra; Mazlan, Shazlina (Universiti Putra Malaysia, 2019)
Higher education institutions in Malaysia have been facing an overwhelming demand to provide adequate facilities and resources to assist with students’ learning. The resources mentioned include ICT facilities, offices, libraries, as well as positive learning environments. Thus, this study aimed to investigate the level of students’ satisfaction with Majlis Amanah Rakyat (MARA) college management services (student service and affairs, registration service, and resources/facilities) and its learning environments. The study also examined the effects of those management services and the learning environments on students’ learning motivations. A descriptive analysis was used to determine the level of students’ satisfaction, while a t-test was used to determine whether student gender influenced students’ satisfaction levels. A total of 169 pre-university students were selected as the sample group, using a convenient sampling method. From the SPSS results, the study found that the level of satisfaction on learning environments and the learning motivations of the participants were high. It also showed that, gender had no influence on the participants’ satisfaction levels. The Smart PLS is a statistical software used for Structural Equation Model (SEM) to know the effect of exogenous variable (independent) on endogenous variable (dependent). SEM-PLS identified that learning environments and student services had an effect on student motivation levels. Moreover, it predicted student satisfaction and motivation levels. Finally, a few recommendations were made for better management service on how to increase a learner’s motivation. © Universiti Putra Malaysia Press.